(Neo)blast from the past: new insights into planarian stem cell lineages. (October 2016) - Zhu, Shu Jun; Pearson, Bret J
Abstract : Collectively, planarian stem cells (neoblasts) are totipotent and are required for tissue homeostasis and regeneration. Recent work has begun to test the long-standing question of whether all neoblasts have the same potential, or whether they actually represent molecularly distinct subpopulations with distinct tissue restriction. Here, we summarize the current state of the field in neoblast lineage organization. It is clear that at least some neoblasts are totipotent, whereas other neoblasts represent functionally distinct molecular subclasses with restricted potential. In addition to neoblast subclasses, tissue-specific progenitors have also been identified, though their ability to proliferate is largely unknown. Together, neoblast lineage development, subclasses, and cell hierarchies are becoming elucidated, showing the complex regulation required for proper tissue homeostasis and regeneration in planarians.